The Effect of Carica Pubescens Lenne and K. Koch Fruit Extract from Dieng Plateau and Cangar to the Amount of Fibroblasts Cells on the Healing of Oral Mucosal Inflammation - Kristanti, Risma Aprinda (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
The purposes of this research are to know the effect of C.pubescens fruit extract on the amount of gingival fibroblasts in wound healing of Rattus norvegicus mouth cavityâ€™s mucosal and to know the effect of C.pubescens comes from two different areas (Dieng and Cangar) on the amount of gingival fibroblasts in wound healing of Rattus norvegicus oral mucosa. Twenty eight rats are divided to be four groups (K1, K2, K3, and K4), each rat is wounded 1 cm on the gingival mucosa of lower jaw (specifically on the apical region of incisive teeth). K1 is the control group with aquadest treatment on the wound. The wound in the K2 is treated with C.pubescens fruit extract from Dieng. The wound in the K3 is treated with C.pubescens fruit extract from Cangar. And the treatment for K4 is medicated by policresulen (common medicine for oral mucosal wound). On the fifth day of the treatment, all rats are sacrificed, and the gingival tissue is taken up for the next step. Gingival tissue is smeared by Haematoxylin Eosin (HE) to analyze the amount of gingival fibroblasts histologically. The result of this research shows that the highest average amount of gingival fibroblasts comes from K4 (policresulen treatment). And there is no significant difference on the number of Rattus norvegicus gingival fibroblasts from all of the groups (K1, K2, K3, and K4).Â Keywords: fibroblast, gingival, wound, mucosa, mouth, C.pubescens